2020
DOI: 10.2147/cmar.s263768
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hypoxic Non-Small-Cell Lung Cancer Cell-Secreted Exosomal microRNA-582-3p Drives Cancer Cell Malignant Phenotypes by Targeting Secreted Frizzled-Related Protein 1</p>

Abstract: Background: Hypoxic environment and exosomes (exos)-mediated intercellular communication are crucial for cancer invasion and metastasis, but the mechanisms are not yet fully understood. In this study, we investigated the regulatory effect of hypoxic tumor cell-secreted exosomal miR-582-3p on non-small-cell lung cancer (NSCLC) cell malignant phenotypes. Methods: The concentration and diameters of exos were evaluated by nanosight particle tracking analysis. microRNA-582-3p (miR-582-3p) expression was detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Physiologically appropriate functioning of cellular process depends on adequate oxygen and energy supply [21]. Hypoxia has been reported to promote metastasis and invasion of NSCLC [22][23][24]. In this study, we found that hypoxia significantly increased the migration and invasion ability of NSCLC cells.…”
Section: Discussionsupporting
confidence: 50%
“…Physiologically appropriate functioning of cellular process depends on adequate oxygen and energy supply [21]. Hypoxia has been reported to promote metastasis and invasion of NSCLC [22][23][24]. In this study, we found that hypoxia significantly increased the migration and invasion ability of NSCLC cells.…”
Section: Discussionsupporting
confidence: 50%
“…MiR-31-5p and miR-582-3p were largely internalized within hypoxic exosomes. Exosomal transfer of miRNAs from hypoxic cancer cells to normoxic cancer cells significantly enhanced the proliferation, migration, and invasion of receptive normoxic lung cancer cells in vitro , and promoted lung adenocarcinoma metastasis ( 77 , 83 ). Similarly, hypoxia induced the upregulation of angiopoietin-like 4 (ANGPTL4), HIF-1α/COX-2 and miR-135b and miR-210 in the exosome cargo of A549 cells, exosome transfer of these factors to other A549 cells led to the enhanced proliferation, migration, angiogenesis, and tumor progression ( 80 , 84 ).…”
Section: Hypoxic Exosomes Promote the Development Of Different Types ...mentioning
confidence: 99%
“…MiR-574-5p has been previously observed that it was upregulated in lung cancer patients vs. controls and that it decreases their expression in PB after surgical resection of the tumor [50]. miR-582-3p has been described as upregulated in hypoxic conditions and is secreted in EVs to promote tumorigenesis [51], and EV-miR-224-5p has been shown to promote tumorigenesis in NSCLC [52]. However, some of these results have been only observed in cell lines, and regardless, their expression has been analyzed in TDV.…”
Section: Discussionmentioning
confidence: 96%